183k views
1 vote
What is -2(3x - 9) + 5x = -10

2 Answers

5 votes

Answer:

x = 28

Explanation:

First, remove the parentheses by distributing -2.

-6x + 18 + 5x = 10

Next, collect the like terms.

-x + 18 = -10

Next, move the constant to the right-hand side and change its sign.

-x = -10 - 18

Next, calculate the difference

-x = -28

Lastly, change the signs on both sides of the equation.

x = 28

These are the steps to answer this equation.

User Markharrop
by
5.0k points
3 votes

Answer:

x=28

Explanation:

-2(3x-9)+5x =-10

now we times -2 to to the inside of the parenthese

giving us

-6x+18 +5x= -10

add like terms

add -6x and 5x

-1x+18=-10

now we add like terms of the constants

minus 18 on both sides

-1x=-28

now divide by -1

x = 28

User Cassianoleal
by
4.9k points